Interfacing of Science, Medicine and Law: The Stem Cell Patent Controversy in the United States and the European Union - Davey, Sonya; Davey, Neil; Gu, Qian; Xu, Na; Vatsa, Rajet; Devalaraja, Samir; Harris, Paul; Gannavaram, Sreenivas; Dave, Raj; Chakrabarty, Ananda (Frontiers in Cell and Developmental Biology, 2015)
The patent eligibility of stem cells – particularly those derived from human embryos – has long been under debate in both the scientific and legal communities. On the basis of moral grounds, the European Patent Office (EPO) has refrained from granting patents for stem cells obtained through the destruction of human embryos. On the contrary, the United States Patent and Trademark Office (USPTO) has historically granted patents regarding the isolation and use of human embryonic and other stem cells. To date, these US patents remain valid despite an increasing onslaught of challenges in court. However, recent precedents established in US courts significantly narrow the scope of patent eligibility within biotechnology. This article compares the implications of recent legal changes on stem cell patent eligibility between the EU and US.